2014
DOI: 10.1097/ta.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine, lidocaine and Mg2+ (ALM) induces a reversible hypotensive state, reduces lung edema and prevents coagulopathy in the rat model of polymicrobial sepsis

Abstract: An ALM bolus/infusion induces a stable, hypotensive hemodynamic state with no arrhythmias, significantly less pulmonary edema, and a higher BT and prevents coagulopathy compared with the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…16,17 In 2012, we further reported that 7.5% NaCl with ALM led to a full correction of platelet-poor plasma prothrombin time (PT) and activated partial thromboplastin time (aPTT) at 60-minute resuscitation. 20,21 Given the clinical significance of early detection and treatment of coagulopathy, the aim of the present study was to expand on our previous work and investigate the timing of 7.5% NaCl with ALM correction using ROTEM in the rat model of severe hemorrhagic shock compared with 7.5% NaCl controls. 20,21 Given the clinical significance of early detection and treatment of coagulopathy, the aim of the present study was to expand on our previous work and investigate the timing of 7.5% NaCl with ALM correction using ROTEM in the rat model of severe hemorrhagic shock compared with 7.5% NaCl controls.…”
mentioning
confidence: 99%
“…16,17 In 2012, we further reported that 7.5% NaCl with ALM led to a full correction of platelet-poor plasma prothrombin time (PT) and activated partial thromboplastin time (aPTT) at 60-minute resuscitation. 20,21 Given the clinical significance of early detection and treatment of coagulopathy, the aim of the present study was to expand on our previous work and investigate the timing of 7.5% NaCl with ALM correction using ROTEM in the rat model of severe hemorrhagic shock compared with 7.5% NaCl controls. 20,21 Given the clinical significance of early detection and treatment of coagulopathy, the aim of the present study was to expand on our previous work and investigate the timing of 7.5% NaCl with ALM correction using ROTEM in the rat model of severe hemorrhagic shock compared with 7.5% NaCl controls.…”
mentioning
confidence: 99%
“…At present, we do not know the relative contributions of adenosine, lidocaine, or magnesium to ALM protection in our rat model of polymicrobial sepsis (9,16). Individually, adenosine and lidocaine have a long history in sepsis research, but neither have realized therapeutic potential in the clinical setting, and hypomagnesemia is a frequent complication of septic and critically ill patients but magnesium therapy for improving outcomes is controversial (44).…”
Section: Figmentioning
confidence: 99%
“…Dual-access vascular ports were fitted within a customized jacket. In CLP rats, a 3-cm midline lapa-rotomy was performed and the cecum was ligated at half the distance between the distal pole and the ileocecal valve (9,18). The ligated portion was punctured once through-and-through with a 21-gauge needle, and a small droplet of stool was milked through each puncture.…”
Section: Animals and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations